How Does AI Improve Surgical Instrument Tracking? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Retained surgical items (RSIs), such as sponges or instruments, are a persistent and dangerous problem in modern medicine. These “never events” can cause ser...
Keywords: AI in Surgery and Robotics; Improve; Surgical; Instrument; Artificial Intelligence; Machine Learning; Deep Learning